A new data mining method for time series in visual analysis of regional economy. Issue 1 (January 2022) - Bai, Yang; Zhao, Min; Li, Rong; Xin, Peizhu
Highlights: We used machine learning algorithms to analyze problems in economic development. Our work combines the time series algorithm to design and plan the system. It indicated that regional economic visualization system has perfect functions. Abstract: In order to improve the effect of visual analysis of regional economy, this paper uses machine learning algorithms to analyze time series data, uses various models and methods of intelligent data analysis to mine data laws from huge data, statistical data reports, and find problems in economic development. Moreover, this paper combines the time series algorithm to design and plan the functional structure of the system, and design a separate module structure from the actual situation of regional economic analysis, and build a model system from the overall structure. After constructing the system, this paper tests the system. From the results of the experimental research, we can see that the regional economic visualization system based on time series constructed in this paper has perfect system functions and can meet the needs of regional economic analysis.